Assistive technology for people with visual disability: Future prospects through a technology foresight exercise. - Cabral, Bernardo; Amorim, Inara; Silva, Daniel; Santana, Islaine; Carvalho, Fernanda; Cordeiro, Vinícius (Technology & Disability, 2023)
BACKGROUND: In recent years, with ever-improving technology, considerable progress has been made in the approaches available to develop mobility assistive technology systems. OBJECTIVE: This paper aims to anticipate the future of assistive technologies of navigation and mobility for people with severe visual disabilities in the next twenty years (2021–2041). METHODS: We conducted a technology foresight exercise by identifying promising technologies and invited over 20,000 researchers worldwide to share their views on the future of assistive technologies for people with visual impairment. The technologies and respondents were identified from specialized journals indexed on Web of Science. RESULTS: Most respondents believe computer vision will be the most important assistive technology group for mobility and navigation for visually impaired people, especially with haptic feedback. They also believe that voice and vibrotactile are the most relevant feedback and that glasses and smartphones will be the most important tools for visual impairment support. CONCLUSIONS: While costs and lack of user training may hamper the development and use of these new technologies, they represent the future of assistive technology for people with visual impairments.